EVALUASI SISTEM INFORMASI MANAJEMEN RUMAH SAKIT DENGAN METODE HOT- FIT DI RSUD SANJIWANI KABUPATEN GIANYAR - Grace Christin Kafiar (ITKM WIDYA CIPTA HUSADA, 2024)
Sanjiwani Regional General Hospital has been using SIMRS since 2008. However, until now a problem has been found, namely the reporting of Report Recapitulation (RL) is still done manually. In addition, there are obstacles by the system, which is supposed to use the latest medical record number, but the system uses the medical record number that has the most history. With these problems, it is necessary to conduct an evaluation to find out the achievements of information system implementation activities and planned follow-up to improve the performance of its implementation. The purpose of this study is to determine the influence of Human, Organization, Technology on the Net Benefit of SIMRS at Sanjiwani Hospital, Gianyar Regency. The design of this study uses a type of observational analytical quantitative research using a cross sectional design. The sample in this study is medical record officers who use the Hospital Management Information System at Sanjiwani Hospital, Gianyar Regency, which totals 32 people. The sample selection technique is purposive sampling. The analysis tool used is multiple linear regression. The results of the study based on the t-count test on human factors obtained a t-count value of 2.762 with a sig value of 0.00 < 0.05 which means that humans have an effect on net benefit. The t-calculation test on the organization factor obtained a t-count value of 2,762 with a sig value of 0.00 < 0.05 which means that the organization has an effect on the net benefit. The t-calculation test on the technology factor obtained a t-count value of 2,218 with a sig value of 0.00 < 0.05 which means that technology has an effect on net benefit. Monitoring and evaluation related to SIMRS are carried out periodically to maintain the quality of SIMRS. Based on the data collected, the researcher assessed that there was an influence found between human factors, organization, and technology on the net benefit at Sanjiwani Hospital, Gianyar Regency.